The Savvy Survey #7: Formatting Questionnaires - Jessica O'Leary; Glenn D. Israel (EDIS, 2016)
The Savvy Survey #7: Formatting Questionnaires is the seventh of the seventeen Savvy Survey Series publications from state specialists with expertise in tailored design survey methodology. Developing a high-quality questionnaire is critical for collecting useful data. After selecting the best questions, the next step is to format them to produce the most effective questionnaire possible. This 7-page publication spotlights several considerations, including question order, layout for best visual appearance, and pagination. Written by Jessica L. Gouldthorpe and Glenn D. Israel, and published by the Agricultural Education and Communication Department, September 2015.